Peningkatan Perhatian dan Hasil Belajar PKn Materi Budi Pekerti melalui Metode Pembelajaran Talking Stick (Penelitian Tindakan Kelas Pada Peserta Didik Kelas I Semester 2 SDN Ngiyono Tahun Pelajaran 2015/2016) - Mashadi, Mashadi (Universitas Sebelas Maret, 2018)
Abstract. The purpose of this study was to increase the attention andlearning outcomes of PKN in the second semester students of class I onBudi Pekerti material at SD Negeri Ngiyono through the Talking Sticklearning method for the 2015/2016 school year. This type of research isClass Action Research conducted in 2 cycles. Subjects of the study wereclass I students, amounting to 18 students consisting of 9 male students and9 female students. Data collection methods used are observation, tests, anddocumentation. The results of the study showed an increase in the attentionand learning outcomes of PKN students. This is shown from the pre cycleaverage value of attention and learning outcomes of students is 71.11 with apercentage of completeness of 35.00% which reaches the value ofcompleteness. In the first cycle the average value of attention and learningoutcomes of students is 79.44 with the percentage of completeness 68.00%while in the second cycle the average value of attention and learningoutcomes of students is 88.33 with a percentage of 96.00% completeness.Attention and learning outcomes of students on PKN subjects Budi Pekertimaterial in class I semester 2 increased with the application of Talking Sticklearning methods and has met the indicator of success that is equal to 75%.